Pemahaman Holistik mengenai Ijarah dalam Hukum Islam: Konsep, dasar hukum, jenis-jenis, syarat, dan rukunnya dalam praktik Muamalah - Syayyidah, Liza Elyvia Nur (Maliki Interdisciplinary Journal, 2024)
Ijarah is a form of contract in Islamic law that has a significant role in the practice of muamalah. This article aims to provide a holistic understanding of ijarah, including its concept, legal basis, types, conditions, and pillars. Through a literature review, it is found that ijarah has a strong legal basis from the Qur’an, Hadith, ijma’, and is supported by the law and DSN-MUI fatwa. Ijarah can be divided into several types based on the object and its utilization. For sharia-compliant implementation, ijarah must fulfill certain conditions and established pillars, although there are differences of opinion among the schools of fiqh. A comprehensive understanding of ijarah is essential to ensure its proper application in the context of modern Islamic economics.